Heart wall is thicker on postmortem computed tomography than on antemortem [corrected] computed tomography: the first longitudinal study. - Hidemi Okuma (Public Library of Science (PLoS), 2013)
Objective To evaluate the postmortem changes of the heart wall on postmortem (PM) computed tomography (CT) in comparison with those on ante mortem CT (AMCT), and in comparison with the pathological findings, obtained in the same patients. Materials and methods We studied 57 consecutive patients who had undergone AMCT, PMCT, and pathological autopsy in our tertiary care hospital between April 2009 and December 2010. PMCT was performed within 20 hours after death, followed by pathological autopsy. The cardiac chambers were measured at five sites on both AMCT and PMCT by two board-certified radiologists who were not provided with clinical information. The differences in heart wall thickness between AMCT with and without contrast medium, between AMCT and PMCT, and between PMCT and pathological anatomy were evaluated statistically. Confounding factors of postmortem change such as gender, presence of arteriosclerosis, the organ related to cause of death, age, and elapsed time since death were examined statistically. Results No significant differences were observed on AMCT in comparison of contrasted and non-contrasted images. The heart wall was significantly thicker on PMCT than on AMCT (p < 0.0001) at all five measurement sites. The heart wall was significantly thicker on PMCT than on pathology specimens when measured in accordance with pathological standard mensuration. However, no significant difference was observed between PMCT measurements and those of pathology specimens at any site when the papillary muscles and epicardial fat were included. No significant association was found between postmortem change in heart wall thickness and gender, presence of arteriosclerosis, the organ related to cause of death, age, or elapsed time since death. Conclusion This is the first longitudinal study to confirm greater thickness of heart wall on postmortem images compared with ante mortem images, in the same patients. Furthermore, the postmortem changes on CT were supported by the pathological findings.